The Effect of Professionalism, Audit Tenure, Time Budget Pressure, Independence and Objectivity on Audit Quality in Public Accounting Firm in Bali Province - Dwi Tarisa; Ni Putu Lisa Ernawatiningsih; Ni Nyoman Ayu Suryandari (www.amertainstitute.com, 2025)
Financial reports that have been audited by a public accountant are more trustworthy than financial reports that are not or have not been audited. Users of audit reports expect that financial reports that have been audited by public accountants are free from errors and can be trusted as a basis for decision making. Audit quality is all the possibilities that exist when an auditor audits a client's financial statements to find violations that occur in the client's accounting system and report them in the form of audited financial reports, where in carrying out the auditor will be guided by relevant auditing standards and accounting codes of ethics. The population in this research are all auditors who work at 19 Public Accounting Firms in Bali Province which are still active. The sample used in this research was 101 respondents based on the questionnaire distributed. The analysis technique used in this research is multiple linear regression analysis. The sampling method used in this research was purposive sampling. The research results show that professionalism, time budget pressure and independence have no effect on audit quality. Meanwhile, the audit tenure and objectivity variables have a positive influence on audit quality at Public Accounting Firms in Bali Province.